Biomarkers of "Linguistic Anxiety" in aphasia: A proof-of-concept case study. (May 2015) - Cahana-Amitay, Dalia; Oveis, Abigail C.; Sayers, Jesse T.; Pineles, Suzanne L.; Spiro, Avron; Albert, Martin L.
Abstract This is a proof-of-concept case study designed to evaluate the presence of "Linguistic Anxiety" in a person with mild aphasia. The participant (aged 68) was tested on linguistic and non-linguistic cognitive tasks administered under conditions that differed in levels of anxiety. A validated anxiety-induction technique rarely used in previous aphasia studies was employed: the participant was instructed to prepare for a public speaking presentation. Measures of linguistic and non-linguistic cognitive performance, and anxiety (self-report and psychophysiologic) were obtained. The participant exhibited increased psychophysiologic stress reactivity (heart rate, skin conductance and self-report ratings) in the high-anxiety condition. In the state of increased anxiety, performance on language tasks, in particular discourse production, declined relative to performance in low-anxiety settings. Even in mild aphasia, language-based anxiety can interfere with language performance. This finding provides a basis for carrying out a study with a larger sample that can open a new path to assessment and treatment of persons with aphasia.